2023
DOI: 10.1002/adma.202307661
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐Induced Regulation of Pt Strain Derived from Pt3Ga Intermetallic for Boosting Oxygen Reduction Reaction

Renjie Gui,
Han Cheng,
Minghao Wang
et al.

Abstract: Pt‐based fuel cell catalysts with excellent activity and stability for proton‐exchange membrane fuel cells (PEMFCs) have been developed through strain regulation in recent years. Herein, this work demonstrates that symmetry‐induced strain regulation of Pt surface of PtGa intermetallic compounds can greatly enhance the catalytic performance of the oxygen reduction reaction (ORR). With the strain environment varies derived from the lattice mismatch of analogous PtGa core but different symmetry, the Pt surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The above-discussed PEM–CCM technology has been extensively utilized in the fields of water electrolysis and fuel cells. 47–56 In particular, such water electrolysis technology has been deeply developed for O 2 generation on space stations. Although traditional water electrolysis technology has been challenging for home O 2 generators due to the production of large amounts of explosive hydrogen at the cathode, adopting the ORR–OER coupled electrocatalytic system may effectively circumvents this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The above-discussed PEM–CCM technology has been extensively utilized in the fields of water electrolysis and fuel cells. 47–56 In particular, such water electrolysis technology has been deeply developed for O 2 generation on space stations. Although traditional water electrolysis technology has been challenging for home O 2 generators due to the production of large amounts of explosive hydrogen at the cathode, adopting the ORR–OER coupled electrocatalytic system may effectively circumvents this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the rational design of the surface strain is pivotal to the development of highly effective HER catalysts, which implies the importance of understanding the correlation between the HER activity and the surface strain. Previous studies have showed that the core in core–shell catalysts plays a crucial role in determining the level of surface strain and the electronic structure of the surface Pt. Currently, there are two classes of widely used core materials: one is disordered alloys (solid solutions), which can induce favorable surface strain; however, the induced surface strains are uneven due to the random and nonuniform elemental distribution of the alloy cores. The other is monometallic cores (e.g., Pd@Pt and Ru@Pt), which can reduce the usage of precious Pt; but these suffer from the limited availability of monometallic materials for Pt skin construction, thereby restricting the range of induced strain.…”
Section: Introductionmentioning
confidence: 99%